Liver mass masquerading as adrenal space-occupying lesion: A rare presentation (Indian Journal of Case Reports, 2024)
Adrenal pseudotumors have been described in the literature; however, liver mass masquerading as adrenal space occupying lesion is a rare entity. Here, we describe the case of a 40-year-old female who presented with right-sided abdominal pain for 1 year and was provisionally diagnosed as non-functioning adrenal adenoma after evaluation. She was planned for laparoscopic adrenalectomy. On laparoscopy, a mass arising from the liver was found. The procedure was abandoned and a computed tomography-guided tru-cut biopsy of liver mass was done, which showed the feature of benign liver tissue suggestive of hepatic adenoma. Later, she underwent an excision of the liver mass. Adrenal pseudotumor should always be kept in mind during surgery for any suspected adrenal mass.